2007
DOI: 10.1161/circresaha.107.153643
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Maturation and Integration of Murine Fetal Cardiomyocytes After Transplantation

Abstract: Abstract-In the present study, we investigated the electrophysiological maturation and integration of immature cardiomyocytes after transplantation; maturation and integration are essential to achieve the cardiac regeneration. Murine fetal cardiomyocytes (FCMs) (d12.5-d15.5) expressing enhanced green fluorescent protein under the control of the ␣-actin promoter were injected into cryoinjured areas and adjacent myocardium of cryoinjured mouse ventricles. Viable short axis tissue slices (thickness, 150 m) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 21 publications
(23 reference statements)
0
77
1
Order By: Relevance
“…*p < 0.05 when compared with blank and GFP controls; #p < 0.05 when compared with the mouse cardiomyocytes (positive control); Dp < 0.05 when compared with the mouse cardiomyocytes, blank control, GFP control, and BMP13 group. signaling between cells and plays an essential role in cell-cell communications in a variety of organ systems including the heart (12,36). The intercalated disk is a cardiac-specific structure that is located in the gap junctions of the myocardial fibers and functions as a bridge connecting the surrounding cardiac myocytes as an electrochemical syncytium through complex chemical information exchanges and electrical impulse conductions among the cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05 when compared with blank and GFP controls; #p < 0.05 when compared with the mouse cardiomyocytes (positive control); Dp < 0.05 when compared with the mouse cardiomyocytes, blank control, GFP control, and BMP13 group. signaling between cells and plays an essential role in cell-cell communications in a variety of organ systems including the heart (12,36). The intercalated disk is a cardiac-specific structure that is located in the gap junctions of the myocardial fibers and functions as a bridge connecting the surrounding cardiac myocytes as an electrochemical syncytium through complex chemical information exchanges and electrical impulse conductions among the cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Cryosurgery was used as a surgical method for introducing injury to the heart (27,41). Mice were placed under anesthesia (100 mg/kg ketamine and 3 mg/kg acepromezine ip) and then positioned face up before insertion of a 22-gauge catheter into the trachea.…”
Section: Methodsmentioning
confidence: 99%
“…For interfering with gap junction activity, mice were subjected to heptanol treatments (27,37). For this study, nine mice were injected with 100 l of 1 mM heptanol iv, which was administered for 3 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…68 Halbach et al found that fetal cardiomyocytes engrafted at the border zone display "electrophysiological plasticity" and maturation in action-potential properties. 69 Identifying the soluble factor(s) that can regulate electrophysiological properties of exogenous SCs might provide a key to improving functional integration and warrants further study.…”
Section: Ly and Nattelmentioning
confidence: 99%